Contribution of solid organ transplant recipients to the pediatric non‐hodgkin lymphoma burden in the United States. Issue 23 (31st July 2017) - Yanik, Elizabeth L.; Shiels, Meredith S.; Smith, Jodi M.; Clarke, Christina A.; Lynch, Charles F.; Kahn, Amy R.; Koch, Lori; Pawlish, Karen S.; Engels, Eric A.
Abstract : BACKGROUND: Pediatric solid organ transplant recipients have a 100 to 200 times higher risk of non‐Hodgkin lymphoma (NHL) than the general pediatric population. Consequently, transplant‐related NHL may contribute considerably to the pediatric NHL burden in the United States. METHODS: A cohort study using a linkage between the US transplant registry and 16 cancer registries was conducted. Cancer incidence rates were calculated for people less than 20 years old in the transplant and general populations. Rates were applied to transplant registry and US census data to estimate pediatric NHL counts for transplant recipients and the general population. RESULTS: During 1990‐2012, an estimated 22, 270 NHLs were diagnosed in US children and adolescents; they included 628 cases diagnosed in transplant recipients. Thus, 2.82% of pediatric NHL diagnoses in the general population (95% confidence interval [CI], 2.45%‐3.19%) occurred in transplant recipients. Among transplant recipients, the most common subtypes were diffuse large B‐cell lymphoma (DLBCL; 64.5% of cases) and Burkitt lymphoma (BL; 8.6%). For DLBCL and BL, transplant recipients contributed 7.62% (95% CI, 6.35%‐8.88%) and 0.87% (95% CI, 0.51%‐1.23%) of diagnoses, respectively. The proportion of NHLs that occurred in transplant recipients was highest among children less than 5 years old (4.46%; 95% CI, 3.24%‐5.69%) and in more recent calendar years (3.73% in 2010‐2012; 95% CI, 2.07%‐5.39%). DLBCL patterns were similar, with transplant recipients contributing 19.78% of cases among children less than 5 years old (95% CI, 12.89%‐26.66%) and 11.4% of cases in 2010‐2012 (95% CI, 5.54%‐17.28%). CONCLUSIONS: Among children and adolescents, solid organ transplant recipients contribute a substantial fraction of NHL diagnoses, particularly DLBCL diagnoses. This fraction has increased over time. Prevention efforts targeted toward this group could reduce the overall pediatric NHL burden. Cancer 2017;123:4663‐4671 . © 2017 American Cancer Society . Abstract : Transplant recipients contribute 2.82% of all pediatric non‐Hodgkin lymphoma diagnoses and 7.62% of all pediatric diffuse large B cell lymphoma diagnoses. Prevention efforts targeted toward solid organ transplant recipients could measurably reduce the overall burden of pediatric non‐Hodgkin lymphoma, particularly diffuse large B cell lymphoma.